(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Meningocele and meningoencephalocele are rare entities produced by herniation of cranial contents at the defective areas of the skull base, which may be congenital, spontaneous or traumatic. The condition may present as CSF rhinorrboea, nasal obstruction or even with meningitis. Managemenl of these basal encephaloceles with endoscopic surgery provides a direct view of the skull base and cause less morbidity compared with transcranial approach. Two cases have been reported here, first, a meningocele presented as a case of recurrent CSF rhinorrhoea and the second one, a meningoencepbalocele presented as recurrent meningitis, treated using an endoscopic procedure and reviews the literature regarding their management.